Kruppel homolog 1 modulates ROS production and antimicrobial peptides expression in shrimp hemocytes during infection by the Vibrio parahaemolyticus strain that causes AHPND - Zheng, Zhou; Liu, Shangjie; Lin, Zhongyang; Aweya, Jude Juventus; Zheng, Zhihong; Zhao, Yongzhen; Chen, Xiuli; Li, Shengkang; Zhang, Yueling (Frontiers in Immunology, 2023)
Shrimp aquaculture has been seriously affected by acute hepatopancreatic necrosis disease (AHPND), caused by a strain of Vibrio parahaemolyticus that carries the Pir toxin plasmids (V. parahaemolyticus(AHPND)). In this study, the transcription factor, Kruppel homolog 1-like of Peneaus vannamei (PvKr-h1), was significantly induced in shrimp hemocytes after V. parahaemolyticus(AHPND) challenge, suggesting that PvKr-h1 is involved in shrimp immune response. Knockdown of PvKr-h1 followed by V. parahaemolyticus(AHPND) challenge increased bacterial abundance in shrimp hemolymph coupled with high shrimp mortality. Moreover, transcriptome and immunofluorescence analyses revealed that PvKr-h1 silencing followed by V. parahaemolyticus(AHPND) challenge dysregulated the expression of several antioxidant-related enzyme genes, such as Cu-Zu SOD, GPX, and GST, and antimicrobial peptide genes, i.e., CRUs and PENs, and reduced ROS activity and nuclear translocation of Relish. These data reveal that PvKr-h1 regulates shrimps’ immune response to V. parahaemolyticus(AHPND) infection by suppressing antioxidant-related enzymes, enhancing ROS production and promoting nuclei import of PvRelish to stimulate antimicrobial peptide genes expression.